Postgraduate education and the sustainability of rainwater supply to riparian communities in the Amazon: from conception to action - Veloso, Nircele Leal; Gonçalves, Cristiane Costa; Mendes, Ronaldo Rodrigues; Sobrinho, Mario Vasconcellos; Costa, Tony Dias; Oliveira, Dênio Carvalho (Revista Brasileira de Pós-Graduação, 2014)
In spite of the wealth of water resources in the Amazon, access to drinking water is still difficult for its population. Water supply in the islands of Belém (PA) is deficient. Local alternatives to guarantee access to water in adequate quantity and quality are a major challenge. The objective of this paper is to present an experience integrating two postgraduate programmes to implement the alternative use of rainwater for drinking purposes in order to improve the sustainability of local water supply. Socioeconomic characterisation and a water supply diagnosis subsidised the implementation of the systems. Sustainability was ascertained by means of the acceptance of and access to the system, financial impacts and water quality standards. In general, these are positive water supply models for riparian populations in the Amazon.